When an equality is set up like this you are going to have 2 answers
Original inequality: -3 ≤ 5 – 2v < 7
When you solve this problem, solve it by making two equations
You will reuse 5-2v in both equation
-3 ≤ 5-2v
&
5-2v < 7
now do simple math
-3 ≤ 5-2v
-8 ≤ -2v
4 ≤ v
however when you divide when you divide by a negative number for an inquality you MUST change the sign to its opposite so
4 ≤ v will be 4≥ v
5-2v < 7
-2v < 2
v < -1
since we divide by a negative in order to get the variable by itself we change the sign to its opposite
v < -1 becomes v > -1